On the periphery of the body: Embodied graffiti and street art research design in a social movement context - Fernández Merino, Francisca Andrea (CAP - Cadernos de Arte Pública / Public Art Journal, 2023)
Every 8th of March or 11th of November, feminist demonstrations are observed worldwide, usually accompanied by performative and artistic expressions. These expressions are articulated mainly through the body: people walking through the streets, dancing, performing, writing on public surfaces, or even painting statements on their faces, chest, or other naked body parts. In this way, the body plays a crucial role in the production and perception of graffiti and political street art within social movements. This implies that the artists and their creative process, as well as those who view and interpret the artwork, are all embodied practices. Embodied methodology connects the experienced moments, senses, cognition, and mobility of both participants and researchers in urban spaces, providing multisensory research results (Fransberg, Myllylä, & Tolonen, 2021). Within this paper, I examine the construction of the context, along with the artists’ and audiences’ encounters and practices -such as felt sense, embodied experience, and aesthetic response-. Additionally, I explore the literature on embodied methodology. All elements are related to the context of Graffiti and Street Art Research (GSAR) in a social movement context.